2019
DOI: 10.1002/cplu.201900133
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oligo(1,8‐pyrenylene)s: A Series of Functional Molecular Liquids

Abstract: A monomer‐through‐pentamer series of oligo(1,8‐pyrenylene)s was synthesized using a two‐step iterative synthetic strategy. The trimer, tetramer, and pentamer are mixtures of atropisomers that interconvert slowly at room temperature (as shown by variable‐temperature NMR analysis). They are liquids well below room temperature, as indicated by POM, DSC and SWAXS analysis. These oligomers are highly fluorescent both in the liquid state and in dilute solution (λF,max = 444–457 nm, φF = 0.80) and an investigation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Those broader and smoother spectra with almost vanished vibronic sub‐bands in 1[2,4‐C 8 C 12 ] and 1[2,5‐C 8 C 12 ] might be due to their greater torsional flexibility [14] . Another hypothesis was the ‘rotamer effect’ resulting from the unrestricted single C−C bond rotation between the vinylene unit and the terminal phenyl rings, and each rotamer might have exhibited a different degree of conjugation [4c,24] …”
Section: Resultsmentioning
confidence: 99%
“…Those broader and smoother spectra with almost vanished vibronic sub‐bands in 1[2,4‐C 8 C 12 ] and 1[2,5‐C 8 C 12 ] might be due to their greater torsional flexibility [14] . Another hypothesis was the ‘rotamer effect’ resulting from the unrestricted single C−C bond rotation between the vinylene unit and the terminal phenyl rings, and each rotamer might have exhibited a different degree of conjugation [4c,24] …”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, those groups were shown to be racemic. 27,50 In the present simulation systems, the atropisomers were evenly mixed. Preliminary simulations at 300 K confirmed that the atropisomers of the phenyl group were exchangeable by thermal fluctuation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Semiconducting LCs have common molecular architecture: rigid π-conjugated units with soft side chains. Over the last decade, our group [1][2][3][4][5][6][7][8][9] and many others [10][11][12][13][14][15][16][17][18][19][20][21][22][23] have inherited this molecular design concept and focused not only on the highly ordered, supramolecular self-assembled structure, but also on the disordered and fluid properties under precisely controlled intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%